Ultra-magnifying narrow-band imaging for endoscopic diagnosis of gastric intestinal metaplasia: a pilot image analysis study - Iwagami, Hiroyoshi; Uedo, Noriya; Yip, Hon-Chi; Shichijo, Satoki; Kanesaka, Takashi; Maekawa, Akira; Yamamoto, Sachiko; Higashino, Koji; Takeuchi, Yoji; Ishihara, Ryu; Nakatsuka, Shin-ichi (Endoscopy International Open, 2021)
Background and study aims Narrow-band imaging (NBI) with or without magnification has recently been used for diagnosis of gastric intestinal metaplasia (GIM). Endocytoscopy is a newly developed endoscopic technique that enables ultra-high (500 ×) magnification of the digestive tract mucosa. This study aimed to analyze the ultra-magnifying NBI characteristics of GIM.Patients and methods This was a retrospective observational study conducted in a cancer referral center. Patients who underwent ultra-magnifying NBI of the gastric mucosa using endocytoscopy were eligible. A soft black cap was used for non-contact observation. We compared the characteristic findings of GIM by ultra-magnifying NBI of metaplastic and non-metaplastic mucosae. A reference standard for GIM in this study was conventional magnifying NBI findings of GIM. Results We obtained 28 images of metaplastic mucosa and 32 of non-metaplastic mucosa from 38 patients. Ultra-magnifying NBI revealed the cobblestone-like cellular structure in the marginal crypt epithelium of metaplastic and non-metaplastic mucosa. Diagnostic values (sensitivity, specificity, accuracy and kappa value [95 % confidence interval]) for the heterogeneous cellular structure and rough contour of the marginal crypt epithelium were 82 % (68 %–96 %), 94 % (85 %–100 %), 88 % (80 %–96 %), and 0.70, and 86 % (73 %–99 %), 94 % (85 %–100 %), 90 % (82 %–98 %), and 0.71, respectively.Conclusions The characteristic ultrastructural features of GIM were identified by ultra-magnifying NBI, warranting validation of diagnostic value in a prospective study.